IDENTIFYING STUDENTS’ DIFFICULTIES IN PRONOUNCING ENGLISH VOCABULARY AT THE TENTH GRADE OF SMTK MO’ALE - Gulo, Theoli (Research on English Language Education, 2023)
Pronunciation is the fundamental aspect in building a communication so that everyone can convey the message or ideas to other people clearly, correctly, and orally. Pronunciation will be a problem if the people who pronounced the words not as the correct pronunciation so that, will be effected on listener or hearer comments or reaction. This research was aimed to identifying students difficulties and the causes of students difficulties in pronouncing English vocabulary at the tenth grade of SMTK Mo’ale. This research designed by using qualitative method. The instruments of data collection were interviewed and documentation by video record. The technique of data analysis were data reduction, data display, and conclusion drawing verification. After analyzing the data, researcher found that students have difficulty in pronunciation such as consonants sounds[ʤ,θ, t∫, ∫, v, c], and vowel sounds[ə-ɑ, ɔ, e-I,ʌ], difficulty in pronouncing close consonant sounds , difficulty in pronouncing all the suffixes tion “∫”, and changes letter into other pronunciation. The causes of students difficulties were (1) Lack of confidence (2) Lack of practice (3) The influence of Indonesian language (4) Difference in spelling, pronunciation, and the meaning (5) Lack of vocabulary. Therefore, the researcher concluded that Identifying Sudents’ Difficulties In Pronouncing English Vocabulary was necessary because it can be primary attention in teaching learning process after knowing the difficulty and the cause of students difficulty. It is suggested that research for all the English teachers, students, and next researcher, hopefully can be used as consideration and refereces to make students can pronounced the word correctly.